1999
DOI: 10.1086/515186
|View full text |Cite
|
Sign up to set email alerts
|

Nontyphoid Salmonella Bacteremia: Age‐Related Differences in Clinical Presentation, Bacteriology, and Outcome

Abstract: In a retrospective study, 80 episodes of nontyphoid salmonella (NTS) bacteremia in children were compared with 55 episodes in adults over a 10-year period. The study disclosed major differences in the predisposition, clinical presentation, and outcome as well as the microbiology of NTS bacteremia in relation to age. Adults were more likely than children to have predisposing diseases (95% vs. 15%, respectively; P < .0001) and to receive prior medications (95% vs. 23%, respectively; P < .0001), particularly immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
123
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(148 citation statements)
references
References 1 publication
20
123
0
5
Order By: Relevance
“…Salmonella is a well-recognized cause of endovascular infection in different anatomic sites, of which mycotic aneurysm of the aorta is considered to be the most frequent (13). Among patients above 50 years of age with non-serovar Typhi Salmonella bacteremia, 7 to 10% have been reported to develop arterial infection (2,5,12). In our patient, the muscular abscess most probably originated from an atherosclerotic plaque that had become infected during a transient bacteremic episode.…”
Section: Case Reportmentioning
confidence: 60%
“…Salmonella is a well-recognized cause of endovascular infection in different anatomic sites, of which mycotic aneurysm of the aorta is considered to be the most frequent (13). Among patients above 50 years of age with non-serovar Typhi Salmonella bacteremia, 7 to 10% have been reported to develop arterial infection (2,5,12). In our patient, the muscular abscess most probably originated from an atherosclerotic plaque that had become infected during a transient bacteremic episode.…”
Section: Case Reportmentioning
confidence: 60%
“…1 Annually, S. enterica alone causes an estimated 155,000 deaths worldwide and at least 350 deaths in the U.S.; it is responsible for up to 78% of NTS endocarditis cases and 57% of NTS pericarditis cases. 4,7 Despite increasing awareness of epidemic NTS and S. enterica infections, clinicians rarely consider them potential causes of endovascular and cardiac infections. Fever (100%), heart murmurs (57%), and heart failure (71.4%) are frequently observed in association with NTS endovascular infections, but antecedent diarrhea is rare.…”
Section: Discussionmentioning
confidence: 99%
“…33 Patients with SLE who have been treated with prednisolone, cyclophosphamide, azathioprine, or methotrexate are more predisposed to NTS septicemia and endocarditis than are patients who do not receive immunoregulatory medication. [6][7][8]33 Structural Heart Disease In the previously mentioned 1978 review, 10 83% of Salmonella endocarditis patients younger than age 50 had underlying valvular disease with predominantly mural (rather than valvular) lesions. In a more recent study, 85.7% of cardiovascular NTS patients had underlying heart conditions that included valve disease, prosthetic valves, and ventricular aneurysms.…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…In their 11-year retrospective study of Salmonella focal infection, Rodrigues et al reported 85% of patients with Salmonella cystitis had concurrent diarrhoea, whereas all patients with Salmonella pyelonephritis had concurrent bacteraemia (2). In addition, adults are more likely to have primary bacteraemia and have a higher incidence of secondary focal infections (15).…”
Section: Discussionmentioning
confidence: 99%